2009
DOI: 10.5194/bg-6-2661-2009
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Iceland Sea acidification from time series measurements

Abstract: Abstract. The Iceland Sea is one part of the Nordic Seas. Cold Arctic Water prevails there and the deep-water is an important source of North Atlantic Deep Water. We have evaluated time series observations of measured pCO 2 and total CO 2 concentration from discrete seawater samples during 1985-2008 for the surface and 1994-2008 for deep-water, and following changes in response to increasing atmospheric carbon dioxide. The surface pH in winter decreases at a rate of 0.0024 yr −1 , which is 50% faster than aver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
55
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 29 publications
(29 reference statements)
13
55
1
Order By: Relevance
“…In the Iceland Sea, measurements [40] demonstrate that the ASH is currently shoaling at a rate of 4 m yr 21 . This shoaling and the general reduction of V a in near-surface waters will result in increased exposure of pteropods to less-saturated waters throughout their diurnal migrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the Iceland Sea, measurements [40] demonstrate that the ASH is currently shoaling at a rate of 4 m yr 21 . This shoaling and the general reduction of V a in near-surface waters will result in increased exposure of pteropods to less-saturated waters throughout their diurnal migrations.…”
Section: Discussionmentioning
confidence: 99%
“…As the CO 2 content of seawater increases in response to uptake of anthropogenic CO 2 , readjustment of seawater CO 2 -carbonate equilibria results in the reduction of pH, carbonate ion concentration [CO 2− 3 ] and saturation state ( ) of calcium carbonate (CaCO 3 ) minerals such as calcite (i.e., calcite ) and aragonite (i.e., aragonite ). Such changes have been observed in the open ocean over the past thirty years, with the CO 2 partial pressure (pCO 2 ) of surface seawater increasing by > 30 %, while pH has decreased by ∼ 0.1 along with [CO 2− 3 ] and values for CaCO 3 minerals (Bates and Peters, 2007;SantanaCasiano et al, 2007;Dore et al, 2009;Gonzalez-Davila et al, 2010;Olafsson et al, 2009;Byrne et al, 2010;Bates et al, 2012). In the open ocean of the North Pacific Ocean, uptake of anthropogenic CO 2 has been shown to reduce the saturation state of CaCO 3 minerals, with the result that the lysocline depth (where = 1) has shoaled by up to 100 m .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Sustained observations and modeling studies have shown that oceanic pH is currently decreasing by 0.02 units per decade and is expected to decrease by up to 0.7 units by the year 2100 as a result of atmospheric CO 2 dissolution in the oceans [Bates, 2007;Caldeira and Wickett, 2003;Olafsson et al, 2009;Santana-Casiano et al, 2007]. This ocean acidification (OA) is predicted to affect marine ecosystems through the alteration of community structure [Fabry et al, 2008]; nutrient cycles [Hutchins et al, 2009]; productivity [Riebesell et al, 2007] and carbon export [Mari, 2008;Schulz et al, 2008].…”
Section: Introductionmentioning
confidence: 99%